PENGARUH PENAMBAHAN VITAMIN C PADA PAKAN NON KOMERSIAL TERHADAP EFISIENSI PAKAN PUYUH PETELUR - Endah Subekti (MEDIAGRO, 2012)
This study aims to determine the effect of vitamin C 250 mg / kg and ​​vitamin C 350 mg / kg of feed to feed non- commercial. One hundred and fifty female quails aged 30 days were randomly placed into a cage with three different kinds of treatment rations . Each treatment was repeated five times ration replicates and each replicate consisted of 10 female quails. Ration of the three treatments are : P0 is the basic ration containing 21.5 % crude protein and metabolizable energy 2600 kcal / kg, the second ration treatment is a basic ration plus vitamin C 250 mg / kg of feed ( P1 ), and a third treatment is a basic ration plus vitamin C 350 mg / kg feed ( P2 ). Feed and water given adlibitum. Data taken during the study includes data feed intake, percentage of egg production, egg weight and feed conversion calculation. Data were analyzed using the variance Complete Design Pattern Unidirectional and if there is a difference followed by a contrast test . The results showed that the addition of vitamin C 250 mg / kg of feed and also the addition of vitamin C 350 mg / kg in quail diet with crude protein content of 21.5 % and 2600 kcal metabolizable energy / kg can increase feed intake, egg production and increase the percentage of increase efficiency of feedutilization. Keywords : Quail, Vitamin C, Feed Efficiency